Empowered Psychotherapy : Teaching Self-Processing. - Langs, Robert (Karnac Books, 1994)
'Self-Processing' is Langs' development of self-analysis. He lays down a detailed technique and ground-rules for using this technique in everyday practice, in order to utilise the encoded impulses and adaptive processes of the client.